The Effectiveness of Constructivist Learning Methods Through The Breakout Room Facility at Zoom Cloud Meeting - Sumarni Sumarni (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
There are a number of variations in foreign language teaching methodologies. The learning paradigm has changed from merely translating and memorizing linguistic structures that are often done by students in Samarinda, turning towards constructivist learning where strategies throughout the learning process are applied by students through the help of teachers.They are currently learning although the strategy cannot be generalized. The strategies have been classified according to their characteristics in the following groups: metacognitive, cognitive, social and affective. In this study, the social strategies carried out through the e-learning platform by our foreign language learners are analyzed as well as constructivist learning, which is closely related to the use of social strategies promoted in this study after previous research (Sumarni. 2018) has described the mapping of foreign language learning strategies and become a reference for more in-depth research this time. For this descriptive statistic investigation, 100 students from the University of 17 August 1945 Samarinda was selected and the instrument of a social strategy questionnaire (adapted by SILL 7.0 Version) was developed based on the strengths of this strategy, namely, asking, cooperating, empathizing and practicing during the method of the constructive learning through The Breakout Room in Zoom Cloud Meeting. In the name of establishing students as a center and to have a higher motivation in online learning during pandemic, this investigation deserves to be used as an appropriate recommendation.